Chapter 14 Ageism in Medication Use in Older Patients (2018)
Published studies have documented increased rates of adverse drug events, hospitalizations, mortality, and higher healthcare costs associated with inappropriate medication use among the population of older adults, in addition to various clinical, psycho-social, and economic risk factors. These risk factors are often directly or indirectly linked to ageism. In particular, inappropriate prescribing, polypharmacy/polyherbacy, and medication nonadherence substantially contribute to the rising prevalence of drug-related problems in older patients, such as cognitive impairment, impaired balance, risk of falls, and hospitalizations. These phenomena are closely connected. They present both risk factors and negative consequences of suboptimal prescribing and lead to a complicated net of multiple pharmacotherapeutic risks. This chapter examines inappropriate medication use (inappropriate prescribing, polypharmacy/polyherbacy, and medication nonadherence) among the older population and highlights their direct and indirect associations with ageism.